2007
DOI: 10.1088/0964-1726/16/5/036
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting from a backpack instrumented with piezoelectric shoulder straps

Abstract: Over the past few decades the use of portable and wearable electronics has grown steadily. These devices are becoming increasingly more powerful. However, the gains that have been made in the device performance have resulted in the need for significantly higher power to operate the electronics. This issue has been further complicated due to the stagnant growth of battery technology over the past decade. In order to increase the life of these electronics, researchers have begun investigating methods of generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
194
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(198 citation statements)
references
References 11 publications
3
194
0
1
Order By: Relevance
“…Energy harvesting from a backpack with piezoelectric strips was reported by Granstrom et al (2007). The traditional strap of the backpack was replaced by one made of PVDF.…”
Section: Backpacksmentioning
confidence: 99%
“…Energy harvesting from a backpack with piezoelectric strips was reported by Granstrom et al (2007). The traditional strap of the backpack was replaced by one made of PVDF.…”
Section: Backpacksmentioning
confidence: 99%
“…One of the attempts to generate energy from human walking by Shenck et al [6] by embedding a combination of piezoelectric PVDF and Lead Zirconate Titanate (PZT) structures in the shoe was successful to power a low energy electronic device. Another attempt to harvest energy from human body motion was by Granstrom et al [8] where these researchers embedded piezoelectric PVDF films into the straps of a backpack. Li et al [2] and Vatansever et al [9] demonstrated that piezoelectric PVDF can be used to generate a continuous power of the order of 100 µW using wind energy at moderate wind speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Granstrom et al [38] developed a theoretical model of an energy harvesting backpack that can generate electrical energy from flexible piezoelectric PVDF films integrated into the straps. It was found that 45.6mW of power could be generated from a complete backpack with two piezoelectric straps with an efficiency of more than 13%.…”
Section: History and Recent Developments On Piezoelectric Energy Harvmentioning
confidence: 99%